2011
DOI: 10.1902/jop.2010.100331
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Histologic Evaluation of a Granular Bovine Bone Biomaterial Used as an Adjunct to GTR With a Bioresorbable Bovine Pericardium Collagen Membrane in the Treatment of Intrabony Defects

Abstract: GTR treatment of intrabony defects with the collagen membrane from bovine pericardium and adjunct implantation of the new bovine bone biomaterial may result in significant clinical improvements that can be maintained over a period of 3 years, and regeneration of cementum and periodontal ligament, but without bone formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 30 publications
2
23
0
1
Order By: Relevance
“…Other studies reported greater CAL gain in deeper than in shallower defects, 45 which may explain why this study and our previous report 11 differ. The use of a GTR barrier may have enhanced the result as found by other investigators reporting similar defect depths as in our study 10,13,14,26 . This assumption is also supported by a recent systematic review on animal studies on the histological outcome of periodontal surgery using GTR or bone replacement grafts (BRGs) alone or combined and compared to OF 46 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Other studies reported greater CAL gain in deeper than in shallower defects, 45 which may explain why this study and our previous report 11 differ. The use of a GTR barrier may have enhanced the result as found by other investigators reporting similar defect depths as in our study 10,13,14,26 . This assumption is also supported by a recent systematic review on animal studies on the histological outcome of periodontal surgery using GTR or bone replacement grafts (BRGs) alone or combined and compared to OF 46 .…”
Section: Discussionsupporting
confidence: 90%
“…Hence, the level of new attachment in the BBM group may be more difficult to detect using CAL or RDD measurements (as discussed below) than by bone sounding. The marginal part of a vertical defect grafted with BBM may be penetrable to probing, supported by findings in human histological investigations 25,26 in which the tissue in marginal parts of BBM‐treated vertical periodontal defects was found to consist of a mixture of BBM and soft connective tissue with downgrowth of junctional epithelium along the root surfaces, in contrast to deeper areas in which BBM was found integrated in vital bone with periodontal ligament inserting into the previously diseased root surfaces. This explanation reflects the description by Melcher 27 of wound healing as a “race of tissues.” In addition, the revascularization of the marginal part of a vertical defect may slightly lag behind the deeper part and in turn may hamper bone formation around the graft marginally 28,29 .…”
Section: Discussionmentioning
confidence: 71%
“…The goal of regenerative periodontal surgery is to predictably restore the tooth's supporting apparatus (i.e., root cementum, periodontal ligament [PDL], and bone), which have been lost following periodontal disease or trauma 1‐3 . Various bone grafts, including autogenous bone, allografts, xenografts, and synthetic alloplasts, have been used with varying degrees of success for the treatment of bone and periodontal defects 4‐12 . One grafting material that has been particularly effective because of its combination of osteoconduction and osteo‐induction is demineralized freeze‐dried bone allograft (DFDBA) 13‐17 .…”
mentioning
confidence: 99%
“…The use of resorbable membranes is now sustained by a large evidence and increased experience levels given the widespread use of these products in recent years. However, in a human study, intrabony defects were treated with GTR and resorbable collagen membranes, and histological evaluations revealed the formation of long junctional epithelium above newly formed cementum and periodontal ligament [33]. Furthermore the study observed that filling material was mostly embedded in connective tissue, without any evidence of bone regeneration [33].…”
Section: The Concepts Of Cell Occlusion and Space Provisionmentioning
confidence: 99%